Artificial Intelligence-Driven Music Biometrics Influencing Customers’ Retail Buying Behavior - Rodgers Waymond; Yeung Fannie; Odindo Christopher; Degbey William Y. (Elsevier, 2022)
This study examines the digital transformation effects of artificial intelligence (AI)-based facial and music biometrics on customers’ cognitive and emotional states, and how these effects influence their behavioral responses in terms of value creation. Using a real-life, major optical retail store in China, 386 customers participated in a five-day experiment with different types of music (enhanced by music-recognition biometrics). The findings show that for utilitarian-type customers in a high-involvement AI purchase condition, music-recognition biometric-induced emotion mediates cognition and behavioral intentions. Both likability and the tempo of the music affect the impact of music on cognition. This study contributes to a better understanding of the relationship between cognition and emotion induced by AI-based facial and music biometric systems in shaping customer behavior and it adds to the atmospheric literature. This is a significant contribution given the paucity of research in the context of the Chinese retail environment, which is now a significant retail market with global importance.